Benefits and barriers for household smart meters’ acceptance - Gumz, Jonathan (2021)
The implementation of smart meters in homes is essential to achieve the goals of modernization of the electricity grid and rational use of energy sources. However, in addition to the implantation of devices in homes, it is necessary to have the consumers’ acceptance due to their fundamental role in reducing electricity usage. This study investigates in the literature which factors influence it positively (benefits) and negatively (barriers) for acceptance. For this, a systematic literature review was carried out using the PRISMA method (Preferred research items for systematic review and meta-analyses). A total of 172 articles were surveyed, of which 42 are applied studies. The results obtained 26 different factors that influence acceptance, with the most important benefits being “better energy management through feedback,” “eco-concern,” and “expectation of financial gain.” In contrast, the most relevant barriers are “threatened security,” “lack of familiarity,” and “associated costs.” Acceptance surveys are still highly concentrated in Europe, the USA, and Australia. It is necessary that developing countries, which are leading the expansion of renewable sources in their energy matrices, also consider investigating the local acceptance of meters to be successful in their implementations.